Reassessment of the electron density in Cu2O using γ‐ray diffraction. Issue 6 (1st December 2014) - Jauch, Wolfgang; Reehuis, Manfred
<x xml:space="preserve">Abstract</x> The electron‐density distribution in Cu2O has been critically reexamined to test controversial conclusions from earlier experimental and theoretical studies. The electron density is derived via multipole refinement of high‐quality single‐crystal diffraction data, collected at room temperature with 316.5 keV gamma radiation. Four γ‐lines in the energy range 200–600 keV have been used to extrapolate extinction‐free low‐order structure factors. The remaining extinction corrections refine to a crystal mosaicity identical to the observed one. There is no support for anharmonic contributions to the thermal parameters. Important features of the derived electron density are (i) a partially filled <inline-graphic xlink:href="ark:/27927/pgh2qnh8p9q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> orbital, (ii) an incomplete ionization of Cu and O, and (iii) no interstitial Cu–Cu charge pileup, thereby refuting the covalent bonding hypothesis.